Pengaruh Pendekatan Reggio Emilia Terhadap Kecerdasan Interpersonal Anak Usia Dini Di Taman Kanak-Kanak - Amelia Jafar; Herlina Hasan; Muhammad Akil Musi; Bonita Mahmud (Ihya Ulum: Early Childhood Education Journal, 2023)
The core components of interpersonal intelligence are the ability to understand oneself and one's limitations, intelligence of mood, motivation, temperament and desire, as well as the ability to self-discipline, understand and respect oneself. This study aims to determine whether there is an effect of using the application of the reggio emilia approach to early childhood interpersonal intelligence in kindergarten. This type of research is quantitative experiment using pretest-posttest nonequivalent control group design. The sample was determined using purposive sampling, the sample in this study amounted to twenty-two children, each consisting of a control class of 15 and an experimental class of 15. The data collection technique in this study was an observation sheet of interpersonal skills. From the results of the study it can be seen that the experimental class with the Reggio Emillia approach is higher than the control class, it can be concluded that there is an effect of the Reggio Emillia approach on the development of interpersonal skills. In the effectiveness test, the use of interpersonal methods in Group B students of Aisyiyah Kindergarten Mamajang Makassar City is quite effective for developing interpersonal skills.